Japanese Encephalitis Virus Genotype III Strains Detection and Genome Sequencing from Indian Pig and Mosquito Vector - Seema R. Pegu; Pranab Jyoti Das; Joyshikh Sonowal; Gyanendra Singh Sengar; Rajib Deb; Ajay Kumar Yadav; Swaraj Rajkhowa; Manjisa Choudhury; Baldev R. Gulati; Vivek Kumar Gupta (Vaccines, 2023)
Japanese encephalitis viruses (JEVs) are globally prevalent as deadly pathogens in humans and animals, including pig, horse and cattle. Japanese encephalitis (JE) still remains an important cause of epidemic encephalitis worldwide and exists in a zoonotic transmission cycle. Assam is one of the highly endemic states for JE in India. In the present study, to understand the epidemiological status of JE circulating in pigs and mosquito, particularly in Assam, India, molecular detection of JEV and the genome sequencing of JEV isolates from pigs and mosquitoes was conducted. The genome analysis of two JEV isolates from pigs and mosquitoes revealed 7 and 20 numbers of unique points of polymorphism of nucleotide during alignment of the sequences with other available sequences, respectively. Phylogenetic analysis revealed that the isolates of the present investigation belong to genotype III and are closely related with the strains of neighboring country China. This study highlights the transboundary nature of the JEV genotype III circulation, which maintained the same genotype through mosquito-swine transmission cycles.